Analisis Kontrastif Pada Bahasa Indonesia dan Bahasa Jawa dalam Cerita Anak Terjemahan: Contrastive Analysis of Indonesian and Javanese in Translated Children's Storybooks - Nurjanah, Elen (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
The purpose of this study is to describe the differences in affixation or affixation in Indonesian and Javanese. This research is a research of contrastive analysis. In this study, the object of the study is suffixes in Indonesian and Javanese. The data in this study was taken from translated children's stories published by the East Java Provincial Language Center. The cultural richness in East Java is reflected in children's stories that contain local wisdom and the values of the people of East Java. The data analysis is focused on the similarities and differences between the two languages. This study explains the similarities and differences between Javanese and Indonesian affixation in translated children's storybooks. This research was conducted using a qualitative method. The result of this study is the discovery of affixations that have similarities, namely (1) the affixes -ng, -n in Javanese and meng-, men-, mem- in the language Indonesian, (2) the affix di- in Javanese and Indonesian which is a passive verbal form that means to do something, as well as the affix di-na in Javanese and di-kan in Indonesian, (3) the affix -an in Javanese and Indonesian which functions to form a derivative noun, and (4) the affix -e and -ne in Javanese and its in Indonesian which means possession, The same goes for Sak-e and Se-nya. The difference between the affixes in Javanese and Indonesian can be seen in (1) the affixes -into Javanese and me- in Indonesian, (2) the affixes -em- and -kan, ne- and ber-, tak-i and ke-an ku.